New insights into the cellular response to radiation using microbeams - Folkard, M; Prise, K; Schettino, G; Shao, C; Gilchrist, S; Vojnovic, B (2005)
Micro-irradiation techniques continue to be highly relevant to a number of radiobiological studies, due to their ability to deliver precise doses of radiation to selected individual cells (or sub-cellular targets) in vitro. The Gray cancer institute (GCI) ion microbeam uses a 1 μm diameter bore glass capillary to vertically collimate protons, or helium ions accelerated by a 4 MV Van de Graaff. Using 3He 2+ ions, 99% of cells are targeted with an accuracy of ±2 μm, and with a particle counting accuracy >99%. Using automated cell finding and irradiation procedures, up to 10,000 cells per hour can be individually irradiated. Microbeams are now being used to study a number of novel 'non-targeted' responses that do not follow the standard radiation model based on direct DNA damage and are now known to occur when living cells and tissues are irradiated. One such response is the so-called 'bystander effect' where unirradiated cells are damaged through signalling pathways initiated by a nearby irradiated cell. This effect predominates at low doses and profoundly challenges our understanding of environmental radiation risk. Furthermore, we now have evidence that simple molecules (such as nitric oxide) are involved in the signalling process, such that it may be possible to chemically influence the bystander response. If so, then this could eventually lead to improvements in the treatment of cancer by radiotherapy. Other studies have shown that the bystander effect is induced with equal effectiveness if either the nucleus or the cytoplasm of a cell is targeted. © 2005 Elsevier B.V. All rights reserved.